2020
DOI: 10.1016/j.bcp.2020.114158
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of type 4 cAMP-phosphodiesterases (PDE4s) in mice induces hypothermia via effects on behavioral and central autonomous thermoregulation

Abstract: Inhibitors of Type 4 cAMP-phosphodiesterases (PDE4s) exert a number of promising therapeutic benefits, including potent anti-inflammatory, memory-and cognition-enhancing, metabolic, and antineoplastic effects. We report here that treatment with a number of distinct PDE4 inhibitors, including Rolipram, Piclamilast, Roflumilast and RS25344, but not treatment with the PDE3selective inhibitor Cilostamide, induces a rapid (10-30 min), substantial (−5°C) and long-lasting (up to 5 h) decrease in core body temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 103 publications
2
23
0
Order By: Relevance
“…Immediately after SAS injection some of the mice did not show their normal behavior but were lying on their abdomen and seemed to be panting. As this behavior has been described to be related to thermoregulation ( McDonough et al, 2020 ), we evaluated the effect of SAS injection on the body temperature of the mice. As presented in Figure 4A , saline-treated xCT +/+ mice showed a normal stress-induced hyperthermic reaction after an i. p. injection ( Olivier et al, 2003 ), with an initial 2°C increase of their body temperature, which normalizes after 120 min (Wilcoxon MSRT compared to baseline, 10 min: p = 0.0020, 60 min: p = 0.0059, 120 min: p = 0.2598).…”
Section: Resultsmentioning
confidence: 99%
“…Immediately after SAS injection some of the mice did not show their normal behavior but were lying on their abdomen and seemed to be panting. As this behavior has been described to be related to thermoregulation ( McDonough et al, 2020 ), we evaluated the effect of SAS injection on the body temperature of the mice. As presented in Figure 4A , saline-treated xCT +/+ mice showed a normal stress-induced hyperthermic reaction after an i. p. injection ( Olivier et al, 2003 ), with an initial 2°C increase of their body temperature, which normalizes after 120 min (Wilcoxon MSRT compared to baseline, 10 min: p = 0.0020, 60 min: p = 0.0059, 120 min: p = 0.2598).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a prior study has shown that inhibition of PDE4 promoted the release of amylase from parotid acinar cells in culture 33 , which is consistent with the notion that βadrenoceptor-and cAMP-dependent saliva secretions are rich in protein 1,2 . Conversely, we propose that in awake mice, PDE4 inhibition may induce salivation via additional, central/neuronal regulations, in line with the high expression of PDE4 in brain 34 and the fact that PDE4 inhibition has been shown to affect other autonomic nervous system regulations including control of body temperature or gastrointestinal motility 17,20 . In an intriguing parallel, although the most widely used drug to induce salivation, Pilocarpine, can induce salivation by acting directly on the salivary glands (see Fig.…”
Section: Distinguishing Central and Direct Effects Of Pde4 Inhibition On Salivationmentioning
confidence: 87%
“…PDE inhibitors were generally administered at a dose of 1 mg/kg (i.p. ), which has been shown to produce ≥50% of maximal efficacy on a variety of acute phenotypes of PDE4 inhibition in mice 17,19,20 , and thus likely reflects ≥50% target engagement.…”
Section: Measurement Of Saliva Secretion Ratementioning
confidence: 99%
“…Core body temperature was measured as described [ 42 ] using a thermocouple thermometer (MicroTherma 2T) with mouse rectal probe (RET-3), both from Braintree Scientific (Braintree, MA, USA), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown recently that PDE4s play a critical role in the autonomic regulation of body temperature in mice and that treatment with PAN-PDE4 inhibitors induces a fast-onset (within 10 min), substantial (up to −5 °C) and long-lasting (up to 5 h) hypothermia in the animals [ 42 ]. Intriguingly, an increasing body of research closely correlates nausea with a significant disturbance in thermoregulation in mammals [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%